2022
DOI: 10.3389/fpubh.2022.921093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the National Reimbursement Drug List Negotiation Policy on Accessibility of Anticancer Drugs in China: An Interrupted Time Series Study

Abstract: ObjectiveSince 2016, the Chinese government has been regularly implementing the National Reimbursement Drug List Negotiation (NRDLN) to improve the accessibility of drugs. In the second round of NRDLN in July 2017, 18 anticancer drugs were included. This study analyzed the impact of the NRDLN on the accessibility of these 18 anticancer drugs in China.MethodsNational hospital procurement data were collected from 2015 to 2019. As measurements of drug accessibility, monthly average of drug availability or defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In this study,our ndings indicate a signi cant increase in the use of generic targeted anti-tumor drugs following policy implementation(305.26%, 167.31%, and 347.94%), consistent with previous studies by Lu et al [20,21]. At the same time, the expenditure of the generic targeted anti-tumor drugs decreased(-81.64%, -43.45%, and − 93.10%), and the DDDc decreased(-85.54%, -85.86%, and − 84.93%), which met the requirements of the NCDP to reduce medicines cost and alleviate the drug burden of patients, which was similar to the results of previous studies [22,23].…”
Section: Drug Utilizationsupporting
confidence: 92%
“…In this study,our ndings indicate a signi cant increase in the use of generic targeted anti-tumor drugs following policy implementation(305.26%, 167.31%, and 347.94%), consistent with previous studies by Lu et al [20,21]. At the same time, the expenditure of the generic targeted anti-tumor drugs decreased(-81.64%, -43.45%, and − 93.10%), and the DDDc decreased(-85.54%, -85.86%, and − 84.93%), which met the requirements of the NCDP to reduce medicines cost and alleviate the drug burden of patients, which was similar to the results of previous studies [22,23].…”
Section: Drug Utilizationsupporting
confidence: 92%
“…Huang et al [11], after the 2016 NDPN policy was implemented, found that the utilization of two anticancer medicines increased and the average daily cost decreased. Zhu et al [58] found that the availability of 18 negotiated medicines in 2017 was improved and the average daily cost was reduced. However, these two studies above had fewer outcome measures and no control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a promising field of cancer treatment, it was of considerable significance to the influence of its high cost, especially for low- and middle-income countries. Since 2016, the Chinese government has been implementing an NDPN policy, aiming to reduce the price of innovative medicines with high clinical value ( 32 , 33 ). High-value innovative medicines, represented by anticancer drugs, have gradually established a value-oriented negotiation access model since 2017 ( 34 ), and pharmacoeconomic evaluation has started to play an important role in drug market evaluation.…”
Section: Discussionmentioning
confidence: 99%